Begonia of Vietnam: an updated checklist, including a new species and a new record - Pham, van The; Dinh, Quang Diep; Nguyen, van Canh; Trinh, Ngoc Bon; Nguyen, Duc Dinh; Nguyen, The Hien; Lin, Che Wei (Phytotaxa, 2021)
Vietnam is an important hotspot for Begonia in Southeast Asia. Due to its broad latitudinal range and varied terrain, it has developed a rich biodiversity of flora, of which the genus of Begonia is one of the most striking taxa. In this study, we provide a checklist of Begonia found in Vietnam, including a new species: B. jubar V.T.Pham & C.W.Lin, which is described and illustrated. In addition, Begonia modestiflora Kurz is recorded for the first time in Vietnam.